2015
DOI: 10.4049/jimmunol.1402211
|View full text |Cite
|
Sign up to set email alerts
|

FOXO1 Mediates RANKL-Induced Osteoclast Formation and Activity

Abstract: We have previously shown that the transcription factor FOXO1 is elevated in conditions with high levels of bone resorption. To investigate the role of FOXO1 in the formation of osteoclasts we examined mice with lineage specific deletion of FOXO1 in osteoclast precursors and by knockdown of FOXO1 with siRNA. The receptor activator of NF-kappa B ligand (RANKL), a principal bone resorbing factor, induced FOXO1 expression and nuclear localization two days after stimulation in bone marrow macrophages (BMMs) and RAW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 41 publications
1
37
0
Order By: Relevance
“…In this group of genes, Forkhead box class O 3a ( Foxo3a encoding Foxo3), a member of the Foxo family of transcription factors, has been reported as a direct target of miR-182 in literature (45). Foxo proteins regulate RANKL-induced osteoclastogenesis (47, 48) and FOXO3 activity is associated with outcomes in infectious and inflammatory diseases including RA (49, 50), which suggest its possible relevance in TNF-α-driven osteoclastogenesis. We also selected Mastermind-like 1 ( Maml1 ) as a gene of interest because of its role as a cotranscriptional regulator that is essential for RBP-J signaling (51), which suggests a potential function of Maml1 in osteoclast biology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this group of genes, Forkhead box class O 3a ( Foxo3a encoding Foxo3), a member of the Foxo family of transcription factors, has been reported as a direct target of miR-182 in literature (45). Foxo proteins regulate RANKL-induced osteoclastogenesis (47, 48) and FOXO3 activity is associated with outcomes in infectious and inflammatory diseases including RA (49, 50), which suggest its possible relevance in TNF-α-driven osteoclastogenesis. We also selected Mastermind-like 1 ( Maml1 ) as a gene of interest because of its role as a cotranscriptional regulator that is essential for RBP-J signaling (51), which suggests a potential function of Maml1 in osteoclast biology.…”
Section: Resultsmentioning
confidence: 99%
“…We found that Foxo3 is also a key miR-182 target in TNF-α-mediated osteoclast differentiation. Despite different functions for different Foxo family members, Foxo1, 3, and 4 proteins have been reported to regulate RANKL induced osteoclast differentiation (47, 48). Our study is the first one investigating the role of Foxo3 in TNF-α mediated osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of FOXO1, FOXO3 and FOXO4 results in reduced expression of antioxidant enzymes and failure to protect against oxidative stress [50]. Interestingly, FOXO1 is induced by RANKL stimulation and has a direct effect in stimulating osteoclast formation [51]. The long-term effects of oxidative stress may be particularly important for long-lived cells such as osteocytes and mesenchymal stem cells.…”
Section: Diabetes Ros and Bonementioning
confidence: 99%
“…Some studies show that FoxO1, 3, and 4 proteins are inhibitors of osteoclastogenesis, 57 whereas others found FoxO1 as a positive regulator. 58 These data indicate that the FoxO family plays an important but complex role in osteoclastogenesis. We found that FoxO3 is an important miR182 target in TNF-mediated osteoclast differentiation.…”
Section: Discussionmentioning
confidence: 91%
“…46 FoxO1 and FoxO3 are well-defined miR182 targets in several biological settings. 55,56 FoxO family members, FoxO1, 3, and 4 proteins, are involved in osteoclast differentiation, 45,57,58 but reported with different functions and mechanisms. Some studies show that FoxO1, 3, and 4 proteins are inhibitors of osteoclastogenesis, 57 whereas others found FoxO1 as a positive regulator.…”
Section: Discussionmentioning
confidence: 99%